2018
DOI: 10.3389/fphys.2017.01039
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Evaluation of Graphene Oxide and Titania Loaded Nafion Membranes in Zebrafish

Abstract: The use of nanomaterials in several application fields has received in the last decades a great attention due to their peculiar properties, but also raised many doubts about possible toxicity when these materials are used for some specific applications, such as water purification. Indeed a careful investigation is needed in order to exclude possible harmful side effects related to the use of nanotechnology. Nanoparticles effects on the marine organisms may depend on their chemical composition, size, surface st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…In contrast to these observations, no obvious oxidative stress with regard to alteration in the activities of SOD, CAT, GSH and MDA enzymes was observed in the liver of adult zebrafish exposed to 250 μg/L sFLG for 24, 48, and 72 h (Lu et al, 2017). Moreover, the enhancement of iNOS mRNA and protein in zebrafish larvae exposed to GO (Pecoraro et al 2018) indicated that reactive nitrogen species (RNS)–mediated pathways were also involved in GO-induced toxicity. HO, the enzyme catalyzes the degradation of heme, is also enhanced by GO (Pecoraro et al, 2018).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to these observations, no obvious oxidative stress with regard to alteration in the activities of SOD, CAT, GSH and MDA enzymes was observed in the liver of adult zebrafish exposed to 250 μg/L sFLG for 24, 48, and 72 h (Lu et al, 2017). Moreover, the enhancement of iNOS mRNA and protein in zebrafish larvae exposed to GO (Pecoraro et al 2018) indicated that reactive nitrogen species (RNS)–mediated pathways were also involved in GO-induced toxicity. HO, the enzyme catalyzes the degradation of heme, is also enhanced by GO (Pecoraro et al, 2018).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Moreover, the enhancement of iNOS mRNA and protein in zebrafish larvae exposed to GO (Pecoraro et al 2018) indicated that reactive nitrogen species (RNS)–mediated pathways were also involved in GO-induced toxicity. HO, the enzyme catalyzes the degradation of heme, is also enhanced by GO (Pecoraro et al, 2018). Although the data are contradictory, all these studies indicate that generation of ROS is able to modulate the expression and functions of antioxidant enzymes either directly or indirectly and have a potential impact on cellular MDA and GSH concentrations.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the toxicity of the TiO 2 nanoparticles in A. mellifera because this xenobiotic is used in a wide range of products, and because there is scant published literature about the toxicity of NPs on terrestrial arthropods. Several studies in literature have shown the non‐toxicity of these nanoparticles in some model organisms (Brundo et al, ; Pecoraro et al, , ; Scuderi et al, ). Our findings proved, titanium dioxide nanoparticles are toxic to all the concentrations considered.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on animal models have shown that NPs can be potentially toxic (Hu et al, ; Lankveld et al, ), and that toxicity of NPs depends certainly on their size (Lankveld et al, ). Among the different animal models, zebrafish or Danio rerio is considered an excellent model for nanotoxicity studies for some particular features of these animals (Brundo et al, ; Lee, Nallathamby, Browning, Osgood, & Xu, ; Pecoraro et al, ; Pecoraro et al, ; Pecoraro et al, ; Salvaggio et al, ; Sarasamma et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%